Gender, womens health care concerns and other social factors in health and health care - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald Publishing Limited, 2018)
This volume of 'Research in the Sociology of Health Care' analyses micro-level gender issues and other social factors impacting macro-level health care systems. Examining the health and health care issues of patients and providers of care both in the United States and in other countries, chapters focus on linkages to policy and population concerns as ways to meet global health care needs.
Prelims -- Introduction to volume -- Gender-and cancer-related issues -- Pregnancy and childbirth -- Use of health care and gender -- Gender issues outside of the US and Europe -- Other gender topics -- Index.
Includes index.
Print version record
Keywords: Women's health services; Medical care -- Sex differences; Cancer in women; Social Science -- Sociology -- General; Medical sociology